Challenges and opportunities of utilizing municipal solid waste as alternative building materials for sustainable development goals: A review - Soni, A. (Elsevier B.V., 2022)
Strict environmental concern, depletion, and price hike of building construction materials are driving scientific studies for the search of alternative materials for building construction. To this end sustainable building materials could be a fruitful solution. This review aims to discern the environmental efficacy of solid waste management (SWM) and its relationship with four stimuli i.e., economic structure, regulatory structure, science, and time. The study also highlights the investigation of governance network to figure out the regulatory structure and governance of waste management. Extensive details on solid waste with their sources, recycling potential and their current utilization for substantial development are outlined. A throughout of the production process, properties, advantages, disadvantages, and the global economy of building material developed through recycling of solid waste are discussed. This article also deals with the sustainability, social, and environmental impact of green building materials. The study identifies the future direction for the effective utilization of solid waste for developing building materials. Further, the scope of the present also focusses on the concept of circular economy for developing construction materials through recycling of solid waste, which provides an easy reference for solid waste processing towards sustainability. Â© 2022 Elsevier B.V.